2005
DOI: 10.1089/ees.2005.22.177
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Mixed Methanotrophic Culture Capable of Chloroethylene Degradation

Abstract: A consortium of methanotrophs cultured from the St. Joseph's aquifer in Schoolcraft, MI, was found to exhibit similar methane consumption rates as pure cultures of methanotrophs. The methanotrophic consortium resides within a portion of the aquifer contaminated with a mixed waste plume of perchloroethylene (PCE) and its reductive dechlorination products from natural attenuation, trichloroethylene (TCE), cis-dichloroethylene (c-DCE), and vinyl chloride (VC). Oxidation kinetics for TCE, c-DCE, and VC were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…sMMO‐expressing cells are able to oxidize a wide range of compounds including aliphatic and aromatic hydrocarbons, and their halogenated derivatives (Burrows et al ., ; Trotsenko and Murrell, ). Similarly, pMMO‐expressing cells, albeit possessing a narrower substrate range (pMMO oxidizes alkanes and alkenes up to C 5 ; Trotsenko and Murrell, ), have been found to degrade mixed pollutants in the laboratory as well as in‐situ (Forrester et al ., ; Lee et al ., ; Paszczynski et al ., ), and even out‐perform sMMO‐expressing cells under specific conditions in the laboratory (Lee et al ., ). Hence, both pMMO‐ and/or sMMO‐expressing cells are applicable for bioremediation.…”
Section: Outlook: Putting Mob Into the Context Of Microbial Resource mentioning
confidence: 98%
“…sMMO‐expressing cells are able to oxidize a wide range of compounds including aliphatic and aromatic hydrocarbons, and their halogenated derivatives (Burrows et al ., ; Trotsenko and Murrell, ). Similarly, pMMO‐expressing cells, albeit possessing a narrower substrate range (pMMO oxidizes alkanes and alkenes up to C 5 ; Trotsenko and Murrell, ), have been found to degrade mixed pollutants in the laboratory as well as in‐situ (Forrester et al ., ; Lee et al ., ; Paszczynski et al ., ), and even out‐perform sMMO‐expressing cells under specific conditions in the laboratory (Lee et al ., ). Hence, both pMMO‐ and/or sMMO‐expressing cells are applicable for bioremediation.…”
Section: Outlook: Putting Mob Into the Context Of Microbial Resource mentioning
confidence: 98%
“…Using competitive RT‐PCR assays developed in our laboratories (Han & Semrau, 2004), we found that methanotrophic cultures in soil slurries and groundwater from a mixed chloroethane/chloroethene plume expressed only pMMO, and not sMMO, and concluded that pMMO‐expressing cells were responsible for the observed chlorinated hydrocarbon degradation at this site (Forrester et al , 2005).…”
Section: Application Of Methanotrophsmentioning
confidence: 99%
“…Cometabolic aerobic degradation is a fortuitous conversion with no clear benefit to the responsible organisms and requires a primary substrate to support microbial growth and energy conservation (Alvarez‐Cohen & Speitel, ). The well‐described cometabolic CAH degradation by methanotrophs (Alvarez‐Cohen & Speitel, ; Forrester et al ., ; Shukla et al ., ) is of interest in hyporheic zones because it can be hypothesized that their activity in upper oxic sediment layers is sustained by methane produced by indigenous methanogens in lower anaerobic layers (Fig. S1).…”
Section: Introductionmentioning
confidence: 98%